Videoconference clinics improve efficiency of inflammatory bowel disease care in a remote and rural setting. (October 2020) - Ruf, Benjamin; Jenkinson, Phillip; Armour, David; Fraser, Mhairi; Watson, Angus JM
Introduction: Patients with inflammatory bowel disease (IBD) require long-term secondary care with periodic specialist follow-up. This can be especially challenging for patients living in remote areas. One possible solution is the implementation of videoconference (VC) clinics as a distance-management tool. Here we assessed the use of VC clinics for IBD in terms of patient safety and economic benefit for patients with IBD living in rural areas in the Scottish Highlands and Islands. Methods: Eighty-eight patients participating in the IBD specialist nurses VC clinic administered via Raigmore Hospital, Inverness, Scotland, UK, between January 2016 and June 2017 were included in this study. A total of 229 appointments were assessed. Results: We found the use of a VC clinic to be safe and effective as only 0.9% of appointments required urgent medical assessment and 92% of the VC clinic appointments resulted in further VC clinic follow-up. A total travelling distance of 72, 245.3 km and a total travelling time of 71, 688 minutes were saved in this patient cohort. It was shown that an average of US36.61 of potential travelling cost could be saved per appointment. Discussion: VC clinics represent a patient-centred participatory model of care for IBD patients living in remote areas with enormous time- and cost-saving potential while being safe and effective. Further investigations into patient satisfaction and the combination with other telemedicine tools such as telephone conferencing and mobile phone applications are needed to evaluate the full potential of the concept.